2005
DOI: 10.1111/j.1365-2044.2004.04106.x
|View full text |Cite
|
Sign up to set email alerts
|

The current practice of tracheostomy in the United Kingdom: a postal survey

Abstract: Summary A postal questionnaire was sent to 228 intensive care units throughout the United Kingdom to determine aspects of current tracheostomy practice. From the number of units responding (n = 178, 78%), the majority (n = 173, 97%) practised percutaneous tracheostomy as opposed to open surgical tracheostomy. The Blue Rhino single dilator was the most popular technique (n = 114, 64%). Percutaneous tracheostomy is increasingly carried out under bronchoscopic guidance (n = 148, 83%); however, there remains consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 14 publications
2
75
0
1
Order By: Relevance
“…Several prospective randomized studies have shown that early PCT (within 48 h) resulted in a shorter time of mechanical ventilation, pneumonia and mortality compared to delayed PCT [29,30]. However, there remains considerable variation in the timing of tracheostomy between centres [31,32].…”
Section: No Patientsmentioning
confidence: 99%
“…Several prospective randomized studies have shown that early PCT (within 48 h) resulted in a shorter time of mechanical ventilation, pneumonia and mortality compared to delayed PCT [29,30]. However, there remains considerable variation in the timing of tracheostomy between centres [31,32].…”
Section: No Patientsmentioning
confidence: 99%
“…9 This technique, described as a bedside procedure, has found widespread acceptance as an alternative method to the conventional open procedure, since it eliminates risks associated to transporting critically ill patients and decreases costs related to the operating room. 1,2,[10][11][12] Both methods have been compared to assess their clinical (morbidity and mortality), surgical (technique), and/or financial (cost) differences, [1][2][3][4][5][6][10][11][12][13][14] but results are controversial, and there are insufficient data to establish a clear superiority of the PDT technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is better tolerated than oral or nasal tracheal intubation and is thought to reduce sedation requirements and time in the intensive care unit (ICU). [1][2][3][4][5][6] Traditionally, elective tracheostomy has been performed in the operating room (OR) by using the standard surgical techniques originally described by Jackson. 7 Ciaglia et al 8 described a percutaneous dilational tracheostomy (PDT) based on a model proposed by Seldinger for endovascular intervention procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Organisational changes within trusts to place tracheostomy and laryngectomy patients on to designated wards will concentrate skills, experience and equipment and provide relevant and consistent medical support, with improvements in patient care described [27,48,49,[142][143][144][145][146].…”
Section: Discussionmentioning
confidence: 99%